Forklift Portable dengan Kapasitas Angkut 100 kg - Robin; La Hasanudin; Prinob Aksar (Piston: Jurnal Teknologi, 2022)
With the development of many industrial warehouses, ranging from warehouses with small capacities to very large indicators, it can become economic and business development in Indonesia. In line with these conditions, the need for tools to increase the size of the large plays an important role in helping the process of moving and arranging the goods produced in the warehouse. The carrier is a set of equipment capable of transferring lifting materials, materials, results, or units of production from one stage of production to another stage of production or from one department to another. This tool is a tool specifically designed to transport, organize and move materials/goods. This tool can also shorten time and make work easier, especially in community businesses such as building shops and grocery store warehouses that require the function of this tool. The manufacture of portable forklifts that are made can facilitate the process of transporting goods from the warehouse to the point of sale. The weight of the goods that can be lifted or transported is 50 kg the lowest and 100 kg the highest according to the capacity of the equipment we make.